2021
DOI: 10.1002/hyp.14317
|View full text |Cite
|
Sign up to set email alerts
|

How do management alternatives of fast‐growing forests affect water quantity and quality in southeastern Brazil? Insights from a paired catchment experiment

Abstract: Fast-growing forest plantations have been expanding in Brazil in the last 50 years, which reach productivities by over 40 m 3 ha À1 year À1 in reduced rotation between 5 and 15 years. In the 1990s, environmental warnings about these plantations guided research projects seeking to understand their effects on water and propose forest management actions to minimize them. The assessment of forest management

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Again, tree water use in plantations is often seen to decline as they mature, with timing varying greatly between species. For example, work has shown that for eucalypts growing under subtropical conditions, a decline in water use sets in after about five years, whereas for pines it varies between 15 and 25 years [120][121][122]. Similar indications of reduced water use at advanced stages of natural regrowth (>35 years) have been reported under temperate conditions [154][155].…”
Section: Recovery Times For Regaining Hydrological Functioning and Ba...mentioning
confidence: 78%
See 2 more Smart Citations
“…Again, tree water use in plantations is often seen to decline as they mature, with timing varying greatly between species. For example, work has shown that for eucalypts growing under subtropical conditions, a decline in water use sets in after about five years, whereas for pines it varies between 15 and 25 years [120][121][122]. Similar indications of reduced water use at advanced stages of natural regrowth (>35 years) have been reported under temperate conditions [154][155].…”
Section: Recovery Times For Regaining Hydrological Functioning and Ba...mentioning
confidence: 78%
“…At the other end of the spectrum, the largest decreases in baseflows have been reported after planting fast-growing exotic tree species (often pines or eucalypts) in areas where average rainfall is insufficient to support (evergreen) forest naturally, and grassland or shrubland is the assumed natural baseline vegetation [57,83]. However, there are indications of gradually diminishing tree water use -and therefore partial streamflow recovery -as these planted forests mature [120][121][122], although evidence from the tropics remains particularly sparse [58,123].…”
Section: Conditions Where Flr Decreases or Increases Baseflowmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, replacing grassland and shrubland with eucalyptus and pine forests in South Africa significantly reduced annual runoff in the succeeding 3-6 years (Scott and Lesch, 1997;Slingsby et al, 2021). In southern Brazil, planting natural forests in the catchment had no significant effect on runoff in the first 2 years (Ferraz et al, 2021), while the planting of eucalyptus forests significantly reduced runoff in the initial 2 years (Iroumé et al, 2021). The Dong Nai River Basin in Vietnam converted natural forests to coffee plantations, significantly increasing surface runoff and reducing underground runoff (Truong et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The most common methods for assessing the impact of climate variability and vegetation change on water resources include hydrological models (Ebodé et al, 2022; Yonaba et al, 2021), multivariable statistical methods (Gebremicael et al, 2019a; Shawul et al, 2019), experimental approaches involving paired catchment studies (Cheng et al, 2017; Ferraz et al, 2021) and analytical techniques such as the elasticity concept and Budyko framework (Gbohoui et al, 2021; Hasan et al, 2018; Wamucii et al, 2021). Despite the uncertainties associated with hydrological model outputs, they remain the most widely used method for assessing the impact of climate variability and vegetation change on water resources due to their ability to explain physical processes to some extent (Addor & Melsen, 2019).…”
Section: Introductionmentioning
confidence: 99%